الحوار بين الأديان: مقاربة مفاهيمية استشرافية في ضوء النقد المعاصر - شكيرب، آسيا (جامعة الأمير عبدالقادر للعلوم الإسلامية - مخبر البحث فى الدراسات العقدية ومقارنة الأديان, 2023)
شهد القرن العشرين محاولات دائبة لتفعيل الحوار، بدأت مع المجمع الفاتيكاني الثاني، ولا زالت تظهر في مستويات فكرية عديدة سعيا منها لتقليص الهوة بين الديانات والإيديولوجيات المختلفة، ووضع أرضية مشتركة لقيم إنسانية جامعة؛ وقد عرف مصطلح "حوار الأديان" الكثير من النقد، فتجاوزه بعض المفكرين سعيا للخروج من الإشكالات المترتبة عن توظيفه؛ كما اقترح البعض مشاريعا مستقبلية تقفز على أطر التعالي وإلغاء الآخر أو تحجيم دوره في العملية الحوارية. نحاول هذه الدراسة تخليص مفهوم حوار الأديان من العوالق التي حالت دون تفعيله على أرض الواقع وحالت دون وجود حوار متكافئ يؤدي إلى التعارف والتقارب والتعايش ضمن أطر قيمية تضمن للطرفين الحفاظ على هويتهم الدينية، كما نسعى إلى تقديم أهم الأطروحات المعاصرة التي تتجاوز عوائق المفهوم سعيا منها لاستشراف حوار ديني فاعل. The twentieth century witnessed tenacious and resolute endeavour to energize dialogue, which began with the Second Vatican Council, and coarry on with the emergence at many intellectual levels in an effort to narrow the gap between different religions and ideologies, and to establish common ground for universal human values. Therefore, the term "interreligious dialogue" has received a lot of criticism, and some thinkers have bypassed it in an attempt to get out of the problems arising from its use. Some also suggested future projects that jump on the frameworks of transcendence, eliminating the other, or limiting his role in the dialogue process. The current study, seeks to analyse the concept of interfaith dialogue, assessing the obstacles that prevented its activation on the ground. It prevented the existence of an equal dialogue that leads to acquaintance, rapprochement and coexistence within value frameworks that guarantee both parties the preservation of their religious identity. We also seek to present the most important contemporary theses that transcend the obstacles of the concept in an effort to anticipate an effective religious dialogue.
Keywords: النقد المعاصر -- العملية الحوارية -- النسق الاصطلاحي